Knowledge, Attitude, and Personal Hygiene Behaviors with Pathological Leukorrhea in Adolescent Girls at SMK 'Aisyiyah Palembang (Association of Public Health Scholars based in Faculty of Public Health, Sriwijaya University, 2021)
Leukorrhea (Vaginal discharge) is one of the reproductive health problems that adolescent girls face. According to research, 75% of women worldwide have experienced leukorrhea. Leukorrhea, alternatively referred to as fluor albus, is a symptom of the female reproductive organs disease that can result in severe complications if left untreated. It is believed that a low level of knowledge, negative attitudes, and bad personal hygiene habits contribute to pathological leukorrhea. The purpose of this study was to examine the effect of knowledge, attitudes, and personal hygiene behaviour on pathological leukorrhea in adolescent girls attending the Vocational High School (SMK) 'Aisyiyah Palembang in 2020. This study used an analytical cross-sectional design and a simple random sampling method with 92 respondents. The results indicated a statistical significance between pathological leukorrhea and knowledge (p-value 0.004), attitude (p-value 0.001), and personal hygiene behaviour (p-value 0.001). Multivariate analysis revealed that the bad personal hygiene behaviour variable (p-value 0.018) was the most determinant associated with pathological leukorrhea (PR = 3.305, 95 per cent confidence interval [CI]:1.232-8.868). This study concludes that persistently bad personal hygiene practices may increase the risk of pathological leukorrhea in adolescent girls. Suggestions for young women to reduce their reliance on pantyliners, wear sweat-absorbing underwear, and avoid tight underwear.